2000
DOI: 10.1080/713649960
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life in older adults with generalized anxiety disorder

Abstract: Improving the quality of life is an important goal in the treatment of psychiatric disorders. The current study described subjective quality of life, or life satisfaction, in a sample of older adults with generalized anxiety disorder (GAD). Patients with GAD were compared to other anxious and nonpsychiatric samples on measures of life satisfaction. Older adults with GAD reported lower quality of life than did nonpsychiatric samples; levels of life satisfaction were comparable between older adults with GAD and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
61
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(67 citation statements)
references
References 51 publications
5
61
1
Order By: Relevance
“…A more recent study reported an internal consistency of the total satisfaction scale of 0.85 in a clinical sample of 217 patients referred for treatment of anxiety and depressive disorders (McAlinden and Oei 2006). In addition, this QOLI has shown strong convergent and divergent validity as well as good construct and criterionrelated validity (McAlinden and Oei 2006;Bourland et al 2000;Grant et al 1995;Frisch et al 1992).…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…A more recent study reported an internal consistency of the total satisfaction scale of 0.85 in a clinical sample of 217 patients referred for treatment of anxiety and depressive disorders (McAlinden and Oei 2006). In addition, this QOLI has shown strong convergent and divergent validity as well as good construct and criterionrelated validity (McAlinden and Oei 2006;Bourland et al 2000;Grant et al 1995;Frisch et al 1992).…”
Section: Methodsmentioning
confidence: 97%
“…The QOLI has demonstrated strong psychometric properties (McAlinden and Oei 2006;Frisch et al 1992;Grant et al 1995;Bourland et al 2000). Frisch et al (1992) used the QOLI in a study with three nonclinical samples and three clinical samples.…”
Section: Methodsmentioning
confidence: 99%
“…Convergent and divergent validity was demonstrated in clinical and nonclinical populations (Frisch et al, 1992). Discriminant validity of the QOLI was also demonstrated in a sample of older adults (Bourland et al, 2000). …”
mentioning
confidence: 99%
“…QOLI has demonstrated strong psychometric properties (Bourland et al 2000;Frisch et al 1992;Grant et al 1995;McAlinden and Oei 2006). One study used the QOLI to measure life satisfaction with three nonclinical samples and three clinical samples (Frisch et al 1992).…”
Section: Methodsmentioning
confidence: 99%